2013
DOI: 10.12659/msmbr.884004
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin induces the apoptosis of human tongue carcinoma cells through the mitochondria-mediated pathway

Abstract: BackgroundPlumbagin, a quinonoid constituent isolated from the root of Plumbago zeylanica L., has been proven to possess anti-tumor activity both in vitro and in vivo. However, its anti-tumor properties for human tongue carcinoma have not been reported. This study aimed to investigate the inhibitory effect and the underlying mechanism of plumbagin on the growth of human tongue carcinoma cells.Material/MethodsCell proliferation ability was detected by EdU incorporation assay and colony formation assay. Cell-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Antimicrobial (Jetty et al, 2010) and anti-cancer activities (Qiu et al, 2013) of this plant are presented recently. In a study that extracts from 50 Taiwanese folk medicinal plants were screened for anti-H. pylori activity, P. zeylanica ethanol extract demonstrated strong anti-H. pylori effects (Wang & Huang, 2005c).…”
Section: Plumbago Zeylanicamentioning
confidence: 99%
“…Antimicrobial (Jetty et al, 2010) and anti-cancer activities (Qiu et al, 2013) of this plant are presented recently. In a study that extracts from 50 Taiwanese folk medicinal plants were screened for anti-H. pylori activity, P. zeylanica ethanol extract demonstrated strong anti-H. pylori effects (Wang & Huang, 2005c).…”
Section: Plumbago Zeylanicamentioning
confidence: 99%
“…Ahmad et al () reported that PL significantly suppressed the growth of estrogen receptor (ER)‐positive MCF‐7 cells and ER‐negative MDA‐MB‐231 cells, with no effect on normal mammary epithelial MCF‐10A cells. Several studies showed that PL‐induced apoptosis through mitochondria‐mediated pathway in human cervical cancer cell lines (Nair et al , ), promyelocytic leukemia cells (Xu and Lu, ), and tongue carcinoma cells (Qiu et al , ). Hafeez et al () recently reported that PL inhibits the growth and metastasis of human prostate cancer PC‐3M cells using an orthotopic xenograft mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Plumbagin, a potential anticancer agent, has been reported to regulate cell proliferation and apoptosis in the development of cancer (21,22). As reported, plumbagin induced colon cancer cell death via a Bak-dependent pathway (23), and promoted tongue squamous cell carcinoma cell arrest at the G2/M phase and apoptosis via p38 MAPk-and PI3k/Akt/mTOR-mediated pathways (24).…”
Section: Discussionmentioning
confidence: 88%